2017
DOI: 10.1086/690206
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐induced pulmonary hypertension in type 2 diabetic mice

Abstract: Hypoxia-induced pulmonary hypertension (HPH) is a progressive disease that is mainly caused by chronic exposure to high altitude, chronic obstructive lung disease, and obstructive sleep apnea. The increased pulmonary vascular resistance and increased pulmonary arterial pressure result in increased right ventricular afterload, leading to right heart failure and increased morbidity. There are several clinical reports suggesting a link between PH and diabetes, insulin resistance, or obesity; however, it is unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 63 publications
(137 reference statements)
0
24
0
Order By: Relevance
“…In contrast, we found that both endothelium‐dependent and independent relaxation in PAs was not altered in T2D mice compared to the control (Pan et al . ). These contrasting results might be due to different diabetic models (i.e.…”
Section: Vascular Function In Hyperglycaemiamentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast, we found that both endothelium‐dependent and independent relaxation in PAs was not altered in T2D mice compared to the control (Pan et al . ). These contrasting results might be due to different diabetic models (i.e.…”
Section: Vascular Function In Hyperglycaemiamentioning
confidence: 97%
“…() showed decreased vascular density in the lung of adult STZ‐induced T1D rats, whereas we have demonstrated a significant increase in vascular density in the lungs of T2D mice (both inducible T2D mice and genetically modified T2D model, KK mice; Pan et al . ). Although we could not find a report on pulmonary vascular density in diabetic patients, there is a report indicating increased pulmonary blood volume and flow in the lung of diabetic patients (Kuziemski et al .…”
Section: Vascular Function In Hyperglycaemiamentioning
confidence: 97%
See 1 more Smart Citation
“…Pan et al reported that elevation of right ventricular pressure due to hypoxia exposure was more pronounced in DM model mice than in their control group, and that increased production of reactive oxygen species and decreased superoxide dismutase were found in the pulmonary arterial endothelial cells of DM mice exposed to hypoxia [ 19 ]. Moral-Sanz et al also reported that hypoxia and DM independently induce pulmonary arterial remodeling and downregulate bone morphogenic protein receptor type 2 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonenzymatic nitration may have less significance in the diabetic lungs as compared to systemic circulation. Therefore, despite locally increased ROS generation in pulmonary vessels [ 16 , 37 , 71 ], in the whole lungs, ROS may not play such an important role in pulmonary circulation of the db/db mice as compared to systemic endothelium.…”
Section: Discussionmentioning
confidence: 99%